Glycerol‐Monolaurate‐Mediated Attenuation of Metabolic Syndrome is Associated with the Modulation of Gut Microbiota in High‐Fat‐Diet‐Fed Mice. Issue 18 (29th August 2019) - Zhao, Minjie; Cai, Haiying; Jiang, Zengliang; Li, Yang; Zhong, Hao; Zhang, Hui; Feng, Fengqin
Abstract : Scope: The gut microbiota plays an important role in the development of diet‐induced obesity and metabolic syndrome. Glycerol monolaurate (GML), a widely consumed food emulsifier, is reported to promote metabolic disorder and gut microbiota dysbiosis in low‐dose supplementation upon low‐fat‐diet feeding. However, little is known about whether GML produce the same effects in mice fed a high‐fat diet (HFD). Methods and results: C57BL/6 mice are fed a HFD with or without GML supplementation (150, 300, and 450 mg kg −1 ) for 10 weeks. The results demonstrated that higher GML treatment (450 mg kg −1 ) ameliorates HFD‐induced metabolic disorders, supported by prevented visceral fat deposition, improved hyperlipidemia, modulated hepatic lipid metabolism, and reduced serum proinflammatory cytokine, TNF‐α. Additionally, all doses of GML attenuated circulating lipopolysaccharide load and insulin resistance. Notably, GML ameliorates HFD‐induced gut microbiota dysbiosis, with increases in Bacteroides uniformis, Akkermansia, Bifidobacterium, and Lactobacillus and decreases in Escherichia coli, Lactococcus, and Flexispira . Spearman's correlation analysis indicates that these enriched specific genera are significantly associated with the metabolic improvements of GML. Conclusion: The findings identify the links between gut microbiota and GML‐induced metabolic improvements, suggesting that the attenuation of HFD‐induced metabolic disorders by higher GML supplementation may occur through targeting gut microbiota. Abstract : Higher‐dose glycerol monolaurate (GML) supplementation improves metabolic syndrome in high‐fat‐diet fed mice by significantly preventing visceral fat deposition, ameliorating hyperlipidemia, modulating hepatic lipid metabolism, reducing insulin resistance, and lowering circulating lipopolysaccharide load, accompanied by gut microbiota modulation. These metabolic improvements are significantly correlated with specific bacterial genera, suggesting the potential of GML in metabolic modulation by targeting gut microbiota.